A Documentary Study of the Integration of Intercultural Communicative Competence in Bhutan’s English Curriculum - Sonam Lhamo; Tashi Wangchuk (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
This study aimed to analyze the integration of Intercultural Communicative Competence (hereby ICC) in Bhutan’s English curriculum for key stage II. ICC is defined in this study as a set of skills that allows one to engage effectively and appropriately with others who are linguistically and culturally different. Bhutan’s English curriculum for key stage II refers to students in grades IV, V, and VI in Bhutan. A documentary research design was employed to analyze one hundred eighteen numbers of classroom activities suggested in the curriculum for students. A Thematic Analysis method was used to analyze the data, which involved deriving codes and categories. The findings of the study revealed the amount of classroom activities related to ICC in Bhutan’s English curriculum is minimal. According to the findings, there is no clear mention of any classroom activity that involves students in understanding various cultures. Based on the findings, the present study discusses Bhutan's English curriculum for key stage II should include a variety of activities in the curriculum that would let students compare different cultures.